Perlindungan Konsumen dan Tanggung Jawab Korporasi dalam Perjanjian Jual Beli Emas: Analisis Kasus PT Antam dan Budi Said - muhammad robeth nujaba; Alfan Dzikria Nurrachamn (CV Rewang Rencang, 2025)
Gold transactions, as a high-value commodity, often use standard agreements that potentially put consumers in a weak position. One prominent case is the dispute between PT Aneka Tambang Tbk (PT Antam) and Budi Said, which culminated in Supreme Court Decision Number 1666 K/Pdt/2022. This dispute demonstrates how the actions of corporate employees can cause significant losses to consumers, raising questions regarding the legal liability of the parent company. This study aims to analyze the liability of PT Antam Tbk using the doctrine of vicarious liability as stipulated in Article 1367 of the Civil Code and Law Number 8 of 1999 concerning Consumer Protection, and examine legal solutions to overcome standard clauses that tend to absolve business actors of responsibility. This study uses a normative juridical method with a statutory, conceptual, and case-based approach. The results of the study indicate that PT Antam Tbk can be held legally responsible for the actions of its employees because these actions were committed within the scope of their work and directly related to the company's business activities. Furthermore, standard clauses that limit or eliminate business actors' responsibilities contradict consumer protection principles and are inconsistent with the principle of balance in contract law. Therefore, there is a need for strengthened regulations, stricter oversight of standard clauses, the application of corporate accountability principles, and increased consumer legal literacy to ensure contractual fairness in gold transactions.